Art In The Age Of... - Ayas, Defne; Hoare, Natasha; Kleinman, Adam; Witte de With - Centre for Contemporary Art, Rotterdam (Rotterdam : Witte de With Center for Contemporary Art, 2015)
Vidokle, Anton ; Thomson, Jon ; Tillmans, Stephan ; Tlalim, Tom ; Vega Macotela, José Antonio ; Salemy, Mohammad ; Schuppli, Susan ; Paglen, Trevor ; Raven, Lucy ; Mul, Marlie ; et al.
Witte de With Center for Contemporary Art, Rotterdam, 23 January 2015 - 3 January 2016 (an exhibition series)
kunstcatalogus